2014
DOI: 10.15517/lank.v13i3.14368
|View full text |Cite
|
Sign up to set email alerts
|

Lankesteriana, a new genus in the pleurothallidinae (orchidaceae)

Abstract: We estimated phylogenetic relationships within Anathallis and related genera using Bayesian analyses of nrITS sequence data. The genus is biphyletic in the molecular trees. A novel generic concept, Lankesteriana, is proposed for the species Anathallis barbulata and 19 close relatives. The genus is more closely related to some species of Trichosalpinx and Zootrophion than to Anathallis s.s. Species previously transferred from Pleurothallis subgen. Acuminatia sect. Acuminatae to Anathallis, are here transferred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 7 publications
2
34
0
1
Order By: Relevance
“…Anathallis, which had traditionally been considered a synonym of Pleurothallis, would be re-considered on the basis of DNA evidence presented by . Anathallis as defined then was latter shown to include a group of species more closely related to some Trichosalpinx (Chiron et al 2012;Karremans 2014), for which genus Lankesteriana was proposed, and a group of species belonging to Stelis s.l. (Chiron et al 2012;Karremans et al 2013a).…”
Section: Affinity Lepanthesmentioning
confidence: 99%
See 2 more Smart Citations
“…Anathallis, which had traditionally been considered a synonym of Pleurothallis, would be re-considered on the basis of DNA evidence presented by . Anathallis as defined then was latter shown to include a group of species more closely related to some Trichosalpinx (Chiron et al 2012;Karremans 2014), for which genus Lankesteriana was proposed, and a group of species belonging to Stelis s.l. (Chiron et al 2012;Karremans et al 2013a).…”
Section: Affinity Lepanthesmentioning
confidence: 99%
“…Not surprisingly, subsequent phylogenetic studies within the Pleurothallidinae have shown that the generic, subgeneric and sectional systematics of the subtribe were not fully resolved. Recircumscriptions and emendations were either made or at least suggested by several authors who used novel analytical methods and/or included a broader sampling of species (Stenzel 2004, Abele 2007, Karremans 2010, 2014, Chiron et al 2012, Karremans et al 2013a, 2013b, Wilson et al 2013, Karremans & Rincón-González 2015, Chiron et al 2016. Meanwhile, hundreds of species' names, either new species or combinations, and dozens of new genera have since then been proposed by Luer (2002aLuer ( , 2004Luer ( , 2005Luer ( , 2006Luer ( , 2007Luer ( , 2009) and others, mostly but not exclusively, on the basis of morphology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…; Luer 2007Luer , 2009) and 1100 species in its broadest circumscription (sensu Pridgeon 2005;Karremans & al. 2013;Karremans 2014Karremans , 2015. Species of Stelis are distributed from Mexico to Central America and the Caribbean, and from Venezuela to Bolivia and Brazil, but the greatest diversity is found along the cordilleras of the Andes (Solano-Gómez 2014).…”
Section: Introductionmentioning
confidence: 99%
“…was re-established by Pridgeon & Chase (2001), and has ever since then, with some exceptions (Luer 2006), received general acceptance by the orchid community (Pridgeon 2005, Pupulin et al 2012, Bogarín et al 2013. Species in the genus are recognised by the tiny habit with ramicauls shorter than the leaf, obtuse petals, a ligulate lip, prominent column wings and naked pollinia that lack caudicles (Karremans 2014).…”
Section: Introductionmentioning
confidence: 99%